O ensino da Expressão Musical e Dramática no 1.º CEB - O caso da Região Autónoma da Madeira. Uma visão curricular - Filipa Barreto de Seabra (Universidade do Minho, 2012)
Revisiting the common places of curriculum, proposed by Schwab (1973) (the student, the teacher, the contents, the curriculum development process and the context), we intend to outline a global analysis of curriculum of Musical and Dramatic Expression in the 1st Cycle of Basic Education in the Autonomous Region of Madeira, Portugal, particularly attaining to the curriculum of Musical Expression, although referring occasionally to the 2nd Cycle of Basic Education and to Arts Education as a whole. The data come from a case study which included documental analysis of a corpus of normative and reference documents and the preliminary analysis of data gathered from the various people involved in the project (coordinators, teachers, students and parents), by survey, interview, focus group, and observation.